Instruments assessing nurse educator's competence: A scoping review - Terhi Lemetti; Anni Pakarinen; Leena Salminen; Heli Virtanen; Toni Haapa (Wiley, 2023)
Abstract Aim The aim of this review was to synthesize the instruments that assess nurse educators' competence. Design A scoping review was conducted with the five‐stage process informed by Arksey and O'Malley. Review Methods The predetermined search strategy was used including an additional hand search. The studies were selected according to inclusion and exclusion criteria to answer the research questions followed: (1) "What instruments are used to assess nurse educators' competence?", (2) "How are the psychometric properties of nurse educators' competence instruments reported in the literature?". The thematic synthesis was used. Data Sources The literature search was conducted in January 2021 using the CINAHL, MEDLINE and ERIC databases from January 2000 to December 2020. Results Of the 1,567 articles searched through, 25 met the inclusion criteria. A total of 19 instruments with 10 areas of competence were identified. Typical competence areas were pedagogical and nursing competence. In addition, leadership in managerial competence was included in several instruments. However, the theoretical backgrounds of the instruments varied and the psychometric properties were reported in varied ways in reviewed studies. Implications for the Profession This study provides evidence about the valid and comprehensive assessment of nurse educators' competence, as competent nurse educators promote excellence in nursing education. To assess a nurse educators' competence comprehensively, a variety of theoretical backgrounds of this competence and more than one instrument for the measurement need to be considered. The selection of the instruments to assess nurse educators' competence should be based on the selected theoretical background and use of valid measurements. Reporting Method This study was reported by following the reporting recommendations of the PRISMA extension for Scoping Reviews (PRISMA‐ScR). Patient or Public Contribution No Patient or Public Contribution was applied, since research design was a scoping review.